SEC proposes rules on adviser business continuity and transition plans. Issue 4 (7th November 2016) - Gordon, Kay
Abstract : Purpose: To discuss the requirements and implications of the US Securities and Exchange Commission's (SEC's) proposed new Rule 206(4)-4, which would require all SEC-registered investment advisers to adopt and implement written business continuity and transition plans (BCPs) reasonably designed to address operational and other risks related to a significant disruption in the investment adviser's operations. Design/methodology/approach: Explains the proposed rules' definition of and specific requirements of BCPs, other requirements relating to annual reviews and record-keeping, practical considerations including advisers' need to update and revise their BCPs, and the SEC's request for comment on issues including possible additional obligations for certain types of clients, reporting of incidents to the SEC, and filing of BCPs with the SEC. Findings: By arguably broadening its approach to the universe of risks that should be addressed in a BCP, the SEC potentially places a higher burden on the advisers to design their BCPs to anticipate all material risks that may become applicable or be responsible for a violation of their fiduciary duties to clients. Practical implications: Given the detailed requirements of the Proposed Rules, including as interpreted by the Proposing Release, it is likely that most registered advisers would have to revisit and revise their BCPs if the rules are adopted. Originality/value: Practical guidance from experienced securities, fund management, regulatory and compliance lawyer.